Public and private sector partners increasingly incorporate agrobiodiversity within a food systems perspective in their work - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
At least 3 private sector (HowGood;FLAG Food Lab Accellerator at Google;WBCSD) and 3 public sector partners (Italy, Peru, India) are incorporating agrobiodiversity and the agrobiodiversity index tool in their work streams and toolbox to support decision-making. The ABD Index is a set of measures to incorporate multiple dimensions of agrobiodiversity into decision-making. Its framework includes three pillars of impact: agrobiodiversity for healthy diets, agrobiodiversity for sustainable production, agrobiodiversity for future options; and three levels of measurement: commitment, actions and status.